Simultaneous Determination of Paracetamol ,Chlorpheniramine Maleate and Ascorbic Acid in Tablet Dosage Form by HPLC - kahtan J. Hasson; Hazim H. Hamdu (College of Pharmacy / Mustansiriyah University, 2012)
The mixture of paracetamol, chlorpheniramine maleate and ascorbic acid is widely used in medicine as anti flu remedy .Pharmaceutically ,this mixture is prepared as a tablet by different manufacturers and it has good reputation in the market .However, this drug mixture is still non-official in pharmacopoiea, but the USP has described a non specific method of HPLC for the mixture of paracetamol with antihistamine and other antitussive drugs . Application of the USP- HPLC method was found unreliable for the analysis of tablet containing this drug mixture of three components, since different chromatographic conditions should be applied for each component. Some workers also prescribed a method of analysis by specific procedure for each component individually after previous extraction, which rather long and tedious. In this work; an HPLC method was developed by using the reversed phase mode of chromatography (ODS column) and a mobile phase consists of ammonium phosphate 0.1M and methanol 20% .the peaks of three components of the studied mixture were well separated and the retention times of ascorbic acid ,chlorpheniramine maleate and paracetamol were 2.10,2.76 and 6.60 Minutes respectively and the whole analysis was accomplished in 10 minutes. The accuracy and precision of this method were approved for the quantitative analysis of each component of the mixture.